Effects of Mantra Meditation versus Music Listening on Knee Pain, Function, and Related Outcomes in Older Adults with Knee Osteoarthritis: An Exploratory Randomized Clinical Trial (RCT). (30th August 2018) - Innes, Kim E.; Selfe, Terry Kit; Kandati, Sahiti; Wen, Sijin; Huysmans, Zenzi
Abstract : Objective . Disease-modifying treatments for OA remain elusive, and commonly used medications can have serious side effects. Although meditation and music listening (ML) have been shown to improve outcomes in certain chronic pain populations, research in OA is sparse. In this pilot RCT, we explore the effects of two mind-body practices, mantra meditation (MM) and ML, on knee pain, function, and related outcomes in adults with knee OA. Methods . Twenty-two older ambulatory adults diagnosed with knee OA were randomized to a MM (N=11) or ML program (N=11) and asked to practice 15-20 minutes, twice daily for 8 weeks. Core outcomes included knee pain (Knee Injury and Osteoarthritis Outcome Score [KOOS] and Numeric Rating Scale), knee function (KOOS), and perceived OA severity (Patient Global Assessment). Additional outcomes included perceived stress (Perceived Stress Scale), mood (Profile of Mood States), sleep (Pittsburgh Sleep Quality Index), and health-related quality of life (QOL, SF-36). Participants were assessed at baseline and following completion of the program. Results . Twenty participants (91%) completed the study (9 MM, 11 ML). Compliance was excellent; participants completed an average of 12.1±0.83 sessions/week. Relative to baseline, participants in both groups demonstrated improvement post-intervention in all core outcomes, including knee pain, function, and perceived OA severity, as well as improvement in mood, perceived stress, and QOL (Physical Health) (p's≤0.05). Relative to ML, the MM group showed greater improvements in overall mood and sleep (p's≤0.04), QOL-Mental Health (p<0.07), kinesiophobia (p=0.09), and two domains of the KOOS (p's<0.09). Conclusions . Findings of this exploratory RCT suggest that a simple MM and, possibly, ML program may be effective in reducing knee pain and dysfunction, decreasing stress, and improving mood, sleep, and QOL in adults with knee OA.